Energy and mass balance modelling for glaciers on the Tibetan Plateau : extension, validation and application of a coupled snow and energy balance model - Huintjes, Eva (Publikationsserver der RWTH Aachen University, 2014)
The Tibetan Plateau is the source region of five of the largest Asian rivers. The large amount of ice, snow and permafrost on the plateau and its surrounding mountain ranges and the stored water therein is important in sustaining seasonal water availability. According to the overall trend of increasing air temperatures on the Tibetan Plateau and its adjacent areas since several decades, most glaciers are retreating. The regional patterns of glacier change are contrasting, influenced by local factors and the spatial and temporal heterogeneity of climate and climate variability. The individual feedback mechanisms between atmosphere and glacier, and the role of the various components of the glacier surface energy and mass balance in the melt process for different climate regions on the Tibetan Plateau have not yet been analysed in detail. This thesis deals with the modelling of glacier surface energy and mass balances on the Tibetan Plateau. Four glaciers and one ice cap on the plateau and its surrounding mountain ranges form the regional study sites: Zhadang glacier (south eastern Tibetan Plateau), Purogangri ice cap (central plateau), Naimona’nyi glacier (western Himalayas), Halji glacier (western Himalayas) and Muztag Ata glacier (eastern Pamirs). The study sites have a maximum distance of approximately equal 1700 km from each other and are located in different climate regions. As it is the case for most remote regions of the world, data availability from in-situ observations is insufficient for more complex, physically-based glacier energy and mass balance models. Hence, we use the in-situ measurement data from the intensive observation period at Zhadang glacier to evaluate the surface energy and mass balance model performance in detail. For decadal model simulations high resolution atmospheric model data from the High Asia Reanalysis is applied. The model scheme couples the atmospheric energy balance to a subsurface multi-layer snow module in order to analyse the atmosphere-cryosphere interactions. For Zhadang ...